A systematic review on external ear melanoma. Issue 7 (July 2015) - Toia, Francesca; Garbo, Giuseppe; Tripoli, Massimiliano; Rinaldi, Gaetana; Moschella, Francesco; Cordova, Adriana
Summary Background External ear melanoma accounts for only 1% of all cutaneous melanomas, and data on its optimal management and prognosis are limited. Aim We aim to review the literature on external ear melanoma to guide surgeons in the treatment of this uncommon and peculiar pathology. Materials and methods A systematic review of English language studies on ear melanoma published from 1993 to 2013 was performed using the PubMed electronic database. Data on epidemiology, oncological treatment (tumor resection and regional lymph nodes management), and reconstruction were extrapolated from selected papers. Results The total number of patients was 858 (30 studies). The helix was the most common location (57%); superficial spreading melanoma was the most common histopathological subtype (41%). The mean Breslow thickness was 2.01 mm, with 88% of stage I–II patients. Sentinel lymph node biopsy was performed in 45% of patients, with 8% of positive nodes. Available data on its prognosis are fragmentary and contrasting, but the Breslow thickness appears to be the main prognostic factor. There is a tendency towards reduced resection margins and preservation of the underlying perichondrium and cartilage. Local flaps are the most popular reconstructive option. Conclusion To the best of our knowledge, this systematic review presents the largest data series on external ear melanoma. There is no general agreement on its surgical management, but a favorable prognosis seems to justify the tendency towards conservative treatments.